Applications of laparoscopic surgery in pediatric patients: a systematic literature review (Research, Society and Development, 2021)
Introduction: laparoscopic surgery is one of the five main fields of progress in pediatric surgery in the last decade of the 20th century and has been a progressive advance that allowed the development of a large number of surgical procedures using minimally invasive technique. However, it is worth analyzing in a special way how this technique is developed in pediatric patients, since there are complications and applications for this population group, which needs careful evaluations when performing procedures. Objective: to analyze case reports, articles and studies that show the advantages and disadvantages of performing videolaparoscopy surgery in pediatric patients Methodology: This is a systematic literature review with studies published in the following databases: National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Virtual Health Library (VHL) and EBSCO Information Services. Relevant sources inherent to the theme were analyzed, using as one of the main criteria the choice of current, original and international articles. After careful reading of the publications, 4 articles were not used due to the exclusion criteria. Thus, there were a total of 12 scientific articles for review. Results: Acute appendicitis proved to be the greatest example of a surgical condition in which the pediatric surgeon can perform videolaparoscopy and offer a better evolution to the patient compared to the conventional technique. However, it was noted that the younger the age, the greater the risk of damage and that this procedure is not recommended, especially in newborns. Conclusion: In children, videolaparoscopy is safely indicated for appendectomy, gallbladder removal, gastroesophageal flow correction, intra-abdominal testis (when the testicle has not descended into the scrotum), ovarian cyst and some types of biopsies.